Impact of social legislation on the criminal law in India - Krishnamurthy, S. (Banglore, 1982)
The task of social reconstruction, the endeavours to bring saccour and relief to the poor, powerless and downtrodden, and the crusade to rid our society from very many social evils are all various manifestations of our collective effort to build a better to-morrow.
Keywords: Social legislation India